Wave 3 weighting and non-response - Sipthorp, M; Misson, S (Wave 3 weighting and non-response [PDF 2.5 MB], 2009)
This paper details the methodology used to calculate the weights for the Wave 3 responding sample of 'Growing Up in Australia, the Longitudinal Study of Australian Children' (LSAC). Wave 1 began in 2004, with the recruitment of a nationally representative sample of 5,107 0-1 year olds (B-cohort) and 4,983 children aged 4-5 years (K-Cohort), selected from the Medicare enrolments database. The methodology for the Wave 3 weighting has been based on the approach taken in Waves 1 and 2, which are outlined. The chapters discuss: General approach to Wave 3 weighting, Estimating Wave 3 response probabilities, Calculating Wave 3 weights, Non-response to instruments, and Instrument response rate by characteristics of families, and an appendix is included on Descriptive statistics for predictor variables of non-response by response status and cohort.
6
Technical paper
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology